Penyuluhan Kader Nahdlatul Ulama Untuk Meningkatkan Aksesibilitas Pendidikan Tinggi Santri - Hastri Firharmawan; Dwi Heriyanto (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Improving the accessibility of higher education for students is an important issue in facing the challenges of globalization and the current development of information technology. This community service aims to illustrate the role of Nahdlatul Ulama (NU) cadres in encouraging the accessibility of NU tertiary institutions for students. In this context, NU cadres act as a liaison between students in the community and NU universities. This community service was carried out in the Bonorowo sub-district, Kebumen Regency in April 2023. The service involved 30 participants using the counseling method. From the results of the service, it was found that the knowledge of the counseling participants related to information on NU higher education including registration procedures, types of scholarships available, available majors, and knowledge about campus life increased. The service team suggested that counseling about the accessibility of NU higher education for students be carried out continuously. It is hoped that continuous counseling will provide more accurate information to prospective students so that it will increase the interest of the santri community to study.